2003
DOI: 10.1542/peds.112.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma Disease and Acute Chest Syndrome in Sickle Cell Disease

Abstract: M pneumoniae is commonly associated with the ACS in patients with sickle cell anemia and occurs in very young children. M hominis should be considered in the differential diagnosis of ACS. Aggressive treatment with broad-spectrum antibiotics, including 1 from the macrolide class, is recommended for all patients as well as bronchodilator therapy, early transfusion, and respiratory support when clinically indicated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(26 citation statements)
references
References 108 publications
0
26
0
Order By: Relevance
“…First described over 30 years ago (Charache et al 1979), ACS has a complex pathophysiology that remains poorly defined. Numerous etiologies have been proposed including typical and atypical bacterial pathogens (Miller et al 1991;Vichinsky et al 2000;Neumayr et al 2003), viral infection (Lowenthal et al 1996), fat embolism (Vichinsky et al 1994), intrapulmonary sequestration of erythrocytes (Vichinsky et al 1994), and nitric oxide -hemoglobin interactions (Gladwin et al 1999).…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…First described over 30 years ago (Charache et al 1979), ACS has a complex pathophysiology that remains poorly defined. Numerous etiologies have been proposed including typical and atypical bacterial pathogens (Miller et al 1991;Vichinsky et al 2000;Neumayr et al 2003), viral infection (Lowenthal et al 1996), fat embolism (Vichinsky et al 1994), intrapulmonary sequestration of erythrocytes (Vichinsky et al 1994), and nitric oxide -hemoglobin interactions (Gladwin et al 1999).…”
Section: Acute Chest Syndromementioning
confidence: 99%
“…In sickle-cell disease, there have been reports of M. pneumoniae causing severe pneumonia in children, with multilobar infiltrates, respiratory distress, and abundant pleural effusion [6,38]. In the United States, Neumayr et al [34] reported multilobar infiltrates and pleural effusion in over 50% of cases with sickle cell disease. Mycoplasma pneumoniae can also cause acute chest syndrome.…”
Section: Mycoplasma Pneumoniae In Special Situationsmentioning
confidence: 99%
“…PPE due to M. pneumoniae has been reported in 4-20% of patients with CAP. Although PPE is generally small, unilateral and does not require chest tube insertion, it can be massive and bilateral 1,[21][22][23][24][25] . In a retrospective observational study involving 121 hospitalized children and adolescent patients with CAP/ PPE, M. pneumoniae without co-infection was detected in 34 and M. pneumoniae/S.…”
Section: Discussionmentioning
confidence: 99%